A meta-analysis of the possible impact of climate change on global cotton yield based on crop simulation approaches. (October 2021) - Li, Na; Yao, Ning; Li, Yi; Chen, Junqing; Liu, Deli; Biswas, Asim; Li, Linchao; Wang, Tianxue; Chen, Xinguo
Abstract: CONTEXT : Cotton is one of the most widely planted fiber crops in the world. Its growth, development, and yield are influenced by elevated atmospheric CO2 concentrations, temperature increases, and seasonal rainfall patterns. However, due to differences in research methods (such as crop models, climate models, and climate scenarios), there are uncertainties in the magnitude and direction of the impact of future climate change on cotton yields in existing studies. OBJECTIVE: To comprehensively assess the potential impact of climate change and adaptation on yieldand analyze the associated uncertainties, 27 published studies (including 1353 samples) were used to establish a meta database of changes in future cotton yield. METHODS: The responses of cotton relative yield change to changes in mean temperature, minimum temperature, maximum temperature, precipitation, and CO2 concentration were studied using local polynomial (Loess) regression in a full dataset. A linear mixed-effect model was then used to explore the quantitative relationship between them in a restricted dataset. RESULTS AND CONCLUSIONS: Using the established full dataset, we found that when the average temperature exceeded 4.3 °C, or the average precipitation decreased or increased too much (>200%), the simulated cotton yield decreased. Elevated CO2 concentrations and appropriate management measures could alleviate the negative impact of climate change. By establishing a linear mixed-effect model, we found that temperature, precipitation, CO2 concentration changes, adaptive measures, study area, climate models, and climate scenarios had significant impacts on cotton yield change. For every 1 °C increase in average temperature, the cotton yield decreased by 1.64%. For every 1% increase in precipitation and 1 ppm increase in CO2 concentration, cotton yield increased by 0.09% and 0.05%, respectively. Cotton yield under adaptation measures was 8.97% higher than without any adaptation. SIGNIFICANCE: The first systematic meta-analysis of the impact of climate change on cotton yield in major cotton-planting regionswas conducted herein. The findings provide new information for policies related to the impact of climate change and enhance our understanding of the future resilience of the cotton system. Graphical abstract: Unlabelled Image Highlights: The change of cotton yield based on model simulation was systematically analyzed by using meta analysis method. The relationships between temperature, precipitation, CO2 and adaptation measures and cotton yield were analyzed. The roles of the number of GCMs in the effects of climate change on cotton yield were systematically analyzed. Temperature, precipitation, CO2 and adaptation measures had significant effects on cotton yields. The variability among different climate models, research sites, and climate scenarios was large.